Karakteristik Kimia dan Sensori Fruit Leather Buah Kuini dan Umbi Bit - Tamba, Frika W; Ayu, Dewi F; Fitriani, Shanti (Universitas Pattimura, 2024)
Chemical and sensory properties of kuini fruit and beetroot was studied by using Completely Randomized Design with five treatments and three replications. The treatments were kuini fruit and beetroot pulp combination, namely KB1 (90:10), KB2 (80:20), KB3 (70:30), KB4 (60:40), and KB5 (50:50). Moisture content, ash content, pH, crude fiber content, total sugar content, antioxidant activity, and sensory assessment (descriptive and hedonic) were observed on the fruit leather. The data obtained were analyzed statistically by using Anova and DNMRT at a α 0.05 level. The results showed that the combination of kuini fruit and beetroot in the fruit leather had a significant effect on moisture content, ash content, pH, crude fiber content, total sugar content, and sensory assessment of the fruit leather. The best treatment in this research was KB2 with characteristics of 9.75% moisture content, 0.84% ash content, 3.46 pH, 4.16% crude fiber content, 63.73% total sugar content, and 181.32 ppm IC50. The best treatment of fruit leather was dark red color, very flavorful kuini fruit, very sweet, and chewy texture that was preferred by panelists for an overall assessment.